IMPLEMENTASI STRATEGI INFORMATION SEARCH DENGAN MEMAKSIMALKAN PENGGUNAAN SMARTPHONE DALAM PEMBELAJARAN PAI KELAS X MIPA 1 DI SMA NEGERI 1 GENTENG TAHUN PELAJARAN 2018/2019 - Nur Laela Dewi; Ahmad Izza Muttaqin; Al Muftiyah (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2019)
The learning strategy used by PAI educators or teachers at SMA Negeri 1 Genteng is an information search strategy using smartphones and utilizing wifi availability and smartphone ownership by students. This research use desciptive qualitative approach. In the process of collecting data using several techniques, namely observation, interview or interview, and documentation. Data analysis techniques using qualitative data analysis. Checking the validity of the data using source triangulation, this study uses a qualitative descriptive approach. Data collection uses techniques, observation, interview or interview, and documentation. Data analysis techniques using qualitative data analysis (data reduction, implementation, and drawing conclusions). Checking the validity of the data uses source triangulation. The application of this strategy to PAI learning is indeed able to optimize the use of smartphones as a learning medium and can increase student activity in learning with evidence that students are able to provide information related to memorization or presentations more smoothly. Supporting factors for this strategy are the availability of wifi networks in schools and smartphone ownership by each student, while for each obstacle that is the lack of enthusiasm of students, rowdy students and wifi networks that suddenly have problems, the PAI teacher has prepared solutions that can be used to overcome obstacles so that learning can still run as it should. Keywords: Implementation, Information Search, Smartphone